REGIONAL FACTORS AS EXPLANATIONS OF POLITICAL CHANGE IN BAJA CALIFORNIA - Herzog, Lawrence A. (Frontera Norte, 2017)
Political geographers have shown increasing interest in explaining the regional dynamics of national political change. This article explores the dimensions of Mexico’s political transformation, focusing on the northern border region. The case of Baja California is examined, and five regional elements are identified as significant: urbanization, regional economic development, integration with the United States, the rise of business elites, and the growth of a border middle class. RESUMEN Los geógrafos políticos han mostrado un interés creciente en explicar las dinámicas regionales de los cambios políticos nacionales. Este artículo analiza las dimensiones regionales de la transformación política de México, enfocado en la región fronteriza del norte. El caso de Baja California sirve como enfoque, y se identifican como importantes cinco factores: la urbanización, el desarrollo económico regional, la integración con Estados Unidos, el crecimiento de grupos empresariales, y la evolución de una clase media fronteriza.